Effect of Selected Factors Influencing Biogenic Amines Degradation by Bacillus subtilis Isolated from Food - Butor, Irena; Jančová, Petra; Purevdorj, Khatantuul; Klementová, Lucie; Kluz, Maciej; Huňová, Ivana; Pištěková, Hana; Buňka, František; Buňková, Leona (Microorganisms, 2023)
Modern food technology research has researched possible approaches to reducing the concentration of biogenic amines in food and thereby enhance and guarantee food safety. Applying adjunct cultures that can metabolise biogenic amines is a potential approach to reach the latter mentioned goal. Therefore, this study aims to study the crucial factors that could determine the decrease in biogenic amines concentration (histamine, tyramine, phenylethylamine, putrescine and cadaverine) in foodstuffs using Bacillus subtilis DEPE IB1 isolated from gouda-type cheese. The combined effects of cultivation temperature (8 °C, 23 °C and 30 °C) and the initial pH of the medium (5.0, 6.0, 7.0 and 8.0) under aerobic and also anaerobic conditions resulted in the decrease of the tested biogenic amines concentration during the cultivation time (another factor tested). Bacillus subtilis was cultivated (in vitro) in a medium supplemented with biogenic amines, and their degradation was detected using the high-performance liquid chromatography equipped with UV-detector. The course of biogenic amines degradation by Bacillus subtilis DEPE IB1 was significantly influenced by cultivation temperature and also the initial pH of the medium (p < 0.05). At the end of the cultivation, the concentration of all of the monitored biogenic amines was significantly reduced by 65-85% (p < 0.05). Therefore, this strain could be used for preventive purposes and contributes to food safety enhance.
Keywords: cultivation; degradation; biogenic amines; Bacillus subtilis